PENGARUH FREKUENSI PEMBERIAN EKSTRAK TANGKAI JARAK CINA (JATROPHA MULTIFIDA) TERHADAP PENYEMBUHAN LUKA PADA MENCIT (MUS MUSCULUS) - Prabawati, Pradnyani (Coping: Community of Publishing in Nursing; Vol 2 No 1 (2014): JURNAL EDISI JANUARI-APRIL 2014, 2014)
Wound  care  is  necessary  in  assisting  the  process  of  wound  healing.  Coral bush contains chemical compounds such as flavonoids that act as anti-bacterial which disrupt the integrity of bacterial cell membranes, coral bush also  contains alkaloids, saponins  and  tannins  that  help  the  healing  process  of  wounds.  This  study  aimed  to determine the effect of frequency giving stalk extract coral bush in wound healing in mice.  This  type  of  research  True  Experiment  with  Post  Test  Only  Control  Group Design. Group one (stalk extract coral bush once daily), group two (stalk extract coral bush twice daily) and group three (NaCl 0.9%  as  control). Sampling technique with Simple Random Sampling by 27 mice. Assessment is done every day in 10 days  by measuring the decrease in mice  skin erythema in the analysis with Color Picker Tool program. The group one average time is 8.11 days of wound healing. Two groups is 6.44 days. Three groups, namely 9.11 days. Krukal Wallis test results showed that the value  Asymp.  Sig  was  0.000  (p  <0.05)  so  that  it  can  be  concluded  that  there  was effect  of  the  frequency  giving  stalk  extract  coral  bush  on  wound  healing  in  mice. Mann  Whitney  test  results  showed  that  the  extract  stalk  coral  bush  twice  a  day  is better than once a day and NaCl 0.9% in mice. Based on these results suggested the use of coral bush in wound healing.
Keywords: stalk extract bush coral; wound healing; decrease the degree of erythema